Work Engagement and Organizational Citizenship Behavior as Predictors of Employees' Job Motivation at PT. Indonesian Tourism Village Dusun Semilir - Tanti Tanti; Sutarto Wijono; Heru Astikasari Setya Murti (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This research aims to determine the simultaneous role or influence of work engagement and organizational citizenship behavior on job motivation. The method used is quantitative, with research techniques employing saturated sampling conducted on 137 employees of PT. Desa Wisata Indonesia, Dusun Semilir. Data were collected using the Utrecht Work Engagement Scale developed by Schaufeli and Bakker (2010), the Organizational Citizenship Behavior scale developed by Organ (1988), and the Job Motivation scale developed by Maslow (1945), which have been tested for validity and reliability. Data were processed using IBM SPSS 25. The research results show that work engagement and organizational citizenship behavior simultaneously predict job motivation among employees. The partial T-test results show that work engagement has an effect on job motivation.